The MI6 and other british spies - Goodman, Michael E. (Ahmedabad : Jaico Publising House, 2021)
Immortalised in popular culture by the James bond novels and movies, unearth the actual nature of the job of a British secret service agent and the evolution of the agency over the ages. The secret service Bureau, the official British intelligence organization was established in 1909. Now known as MI6, this organization has seen the evolution of espionage. Today, they concentrate their efforts in uncovering secrets related to Wars in places like Kuwait and Iraq, Combating terrorism and getting to the roots of the attacks on the London public transit system in 2005.
Includes bibliographical references and index.
Keywords: International Relation